Learn Energy Sources With Interactive Learning Multimedia - Suwiantini, Luh Amay; Jampel, I Nyoman; Astawan, I Gede (Jurnal Ilmiah Sekolah Dasar, 2021)
The low learning motivation of students is caused by the use of learning media, especially in science learning which is still not optimal. This study aims to create interactive multimedia-based learning media on the topic of energy sources for grade IV elementary schools. This research is development research using the ADDIE model. In this study, the implementation and evaluation stages were not carried out due to time constraints and the current condition of the COVID-19 pandemic. The subject of this research is interactive multimedia-based learning media which is assessed by 2 material experts, 2 media experts, 2 design experts, and 2 practitioner experts as well as individual testing by 3 students and small group testing by 6 students. and the object of this research is the validity of interactive multimedia-based learning media. The data collection method used in this research is the questionnaire method. The data analysis technique used in this research is descriptive qualitative and quantitative analysis. The results showed that the media quality of 1) material experts were at a value of 94.63% (very good). 2) Media experts are at a score of 93.33% (very good). 3) design expert is at 91.66% (very good). 4) Expert Practitioners are at a score of 91.66% (very good). 5) individual trials are at a value of 96.11% (very good). 6) The small group trial was at a value of 94.77% (very good). So the interactive multimedia-based learning media produced are very well qualified and worthy to be used in the teaching and learning process.